MORPHOLOGY AND RESISTIVITY VALUE OF FLOURINE-DOPED TIN OXIDE (FTO) USING INDONESIAN LOCAL DIMETHYLTIN DICHLORIIDE (DTMC) PRECURSORS - Rizki, Apti Mira; Yunita, Fariza Eka; Lalasari, Latifa Hanum; Irawan, Januar; Arini, Tri; Firdiyono, Florentinus; Andriyah, Lia; Natasha, Nadia Chrisayu; Yuwono, Akhmad Herman (Metalurgi, 2022)
Transparent Conductive Oxide (TCO) is the main component for solar cell fabrication. One of the promising types of TCO is fluorine-doped tin oxide (FTO). The method used in depositing the conductive layer of FTO is spray pyrolysis with an ultrasonic nebulizer. The precursor is a local Indonesian product, dimethyl tin dichloride (DMTC), with doping ammonium fluoride (NH4F). The variable that used in this study were variations in deposition time (5. 10. 15. 20, and 25 minutes) with a fixed substrate temperature at 300°C and doping variations (un-doped, 2 wt.% doped and 8 wt.% doped) to see the effect of adding F doping to the precursor solution. The resistivity value with deposition time of 5. 10. 15. 20 and 25 minute (2 wt.% doped) is 0.218x100; 0.449x10-1; 1,567x10-2; 0.676x10-2 0.377x10-2 Ω.cm. For doping variations (un-doped, 2 wt% doped and 8 wt% doped) the value is 0.883x10-2; 0.377x10-2; 0.506x10-3 Ω.cm. There is a decreasing trend in the resistivity values obtained along with the increase in deposition time and the addition of doping to obtain better conductive properties. The grain size will increase with increasing deposition time and the addition of doping. The optimum resistivity value obtained in this study was 0.377x10-2 Ω.cm, obtained at the deposition time of 25 minutes with 2 wt.% doping.